From “Context” to “Paratext”: : A Case Study of Robert Desnos’s poem “Demain” - Udomsilpa, Warunee (Journal of Letters, 2023)
In Seuils (1987), French narratologist Gerard Genette presents the notion of “paratext” and explains that each of the paratext’s elements is regarded as having a literary function. This article attempts to apply this notion to analyze “Demain”, a poem in État de veille, a collection of poetry composed by early the twentieth century French poet Robert Desnos. The findings demonstrate that the notion of paratext not only helps readers comprehend the essential meaning of the poem but also enables them to examine the poem more profoundly and to come up with a variety of interpretations. Paratext can also function effectively with the poem’s historical context and the poet’s biography, thereby proving useful for textual analysis.